Redeem your past: Teaching challenges and hopes behind bars - Esther Jawing; Sabariah Abd Rahim; Abang Mohd. Razif Abang Muis; Mohd Nur Hidayat Hasbollah Hajimin; Nadiawati Mahmood; Siti Hasnah Tanalol (Secholian Publication, 2022)
Prison is often perceived negatively due to its purposes such as retribution, incapacitation, deterrence, and rehabilitation for people who are legally held for a crime they have committed. However, the prison institutions are serving a larger-than-life mission to transform the inmates’ life which includes correctional education. This study investigated the challenges faced by teachers in prison schools. Utilizing a qualitative research design, this case study involved seven teachers from the prison Integrity School for young inmates. The interview data were analyzed based on Braun and Clarke’s thematic framework. Findings showed teaching challenges such as pedagogy, teaching and learning materials, policy and opportunities. Another emerging theme points to the hopes harbored to further improve educational attainment in prison. This has led to several suggestions such as (1) modules and skills-based course development to focus on young inmates serving short prison terms (minimum of 3 months); and (2) fluid and organic pedagogical approaches. Drawing upon Nelson Mandela’s famous quote, ‘education is the most powerful weapon you can use to change the world’, this study is addressing more insights to add value to the young inmates’ educational opportunities in prison school. Serving time in prison does not deter the inmates from pursuing their education because they deserve a second chance to reclaim their life post-prison term.